Preliminary assessment of the effect of plant protease inhibitors on the expression of heterologous genes in plant cells / Nassim Khalighi - Khalighi, Nassim (2012)
Despite the successful development of pant-based expression systems for the production of a wide range of recombinant proteins in recent years, there remain serious limitations in the final yield accumulation of the foreign protein in the plant cells used. Plant protease activity represents a significant barrier to efficient and hence economical recombinant protein production. Inadequate information is available on specific plant proteases and its role in foreign protein degradation. Some strategies have been reported recently to overcome endogenous plant protease effects on foreign protein integrity and activity in plants including the co-expression of recombinant proteases to reduce the endogenous protease activity. The lack of information in this area suggests that more studies should be carried out to assess different plant protease inhibitors for the improvement of the stability of foreign protein production in particular host plants. The aim of this research was to evaluate the effect of recombinant plant protease inhibitors on the expression of a cloned heterologous ScFv antibody gene in plant cells. The recombinant tomato Cathepsin D Inhibitor (CDI) gene fused to a KDEL sequence was ligated to a previously construcuted recombinant antibody (scFv) gene developed against toxoplasmosis epitopes (pCTOXO-CDI-KDEL) and then transferred successfully into Nicotiana tabacum cv. BY-2 cell suspension using Agrobacterium-mediated transformation method. In addition, the scFv gene was also ligated to a construct containing only the endoplasmic reticulum retention signal, KDEL, (pCTOXO-KDEL) and this was also transferred into tobacco cells as a comparison against CDI-KDEL containing cells. Both constructs contained GUS marker gene. To assess the effect of the CDI gene in putative transformed tobacco cells GUS fluorometric assay was performed. Total soluble protein of the tobacco cells was also analyzed by Bradford protein assay. The tobacco cells carrying the CDI protease inhibitor gene showed higher TSP levels in comparison with plant cells lacking this iv gene. This finding suggests the positive effect of co-expression of the CDI gene on the expression of scFv anti-toxoplasmosis in tobacco cells. However, quantitative GUS enzymatic activity expressed in pmol 4-MU/mg protein/min did not show any significant differences between two constructs in paired t-test (p>0.05). Overall results suggest that this strategy could be viable for increasing the production of ScFv antibodies in plant cells.